2017
DOI: 10.1111/mec.14095
|View full text |Cite
|
Sign up to set email alerts
|

Asexual queen succession mediates an accelerated colony life cycle in the termite Silvestritermes minutus

Abstract: Mixed modes of reproduction, combining sexual processes with thelytokous parthenogenesis, occur in all major clades of social insects. In several species of termites, queens maximize their genetic input into nondispersing replacement queens through parthenogenesis, while maintaining genetically diverse sterile offspring and dispersing reproductives via sexual reproduction. This so-called asexual queen succession (AQS) has multiple independent origins and its presumed advantages are diverse as well, ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Hence, our model matches well with the reproductive systems of a broad range of termite species. Note that recent studies identified three AQS species in higher termites(Termitidae), which arephylogeneticallydistant from the lower termite genus Reticulitermes (Fougeyrollas et al 2015(Fougeyrollas et al , 2017Fournier et al 2016). The termitid species with AQS exhibit different mechanisms of parthenogenesis: Cavitermes tuberosus uses automixis with terminal fusion (Fournier et al 2016), resulting in homozygous female parthenogens as in Reticulitermes, whereas Embiratermes neotenicus and Silvestritermes minutus use automixis with central fusion, resulting in heterozygous parthenogens (Fougeyrollas et al 2015(Fougeyrollas et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, our model matches well with the reproductive systems of a broad range of termite species. Note that recent studies identified three AQS species in higher termites(Termitidae), which arephylogeneticallydistant from the lower termite genus Reticulitermes (Fougeyrollas et al 2015(Fougeyrollas et al , 2017Fournier et al 2016). The termitid species with AQS exhibit different mechanisms of parthenogenesis: Cavitermes tuberosus uses automixis with terminal fusion (Fournier et al 2016), resulting in homozygous female parthenogens as in Reticulitermes, whereas Embiratermes neotenicus and Silvestritermes minutus use automixis with central fusion, resulting in heterozygous parthenogens (Fougeyrollas et al 2015(Fougeyrollas et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Note that recent studies identified three AQS species in higher termites(Termitidae), which arephylogeneticallydistant from the lower termite genus Reticulitermes (Fougeyrollas et al 2015(Fougeyrollas et al , 2017Fournier et al 2016). The termitid species with AQS exhibit different mechanisms of parthenogenesis: Cavitermes tuberosus uses automixis with terminal fusion (Fournier et al 2016), resulting in homozygous female parthenogens as in Reticulitermes, whereas Embiratermes neotenicus and Silvestritermes minutus use automixis with central fusion, resulting in heterozygous parthenogens (Fougeyrollas et al 2015(Fougeyrollas et al , 2017. Although there is no genetic difference between the founder queen, which is derived from an alate, and her parthenogenetic daughters in the latter species, the parthenogenetic daughters (carrying only maternal chromosomes) also have a higher propensity to develop into neotenic queens than sexually produced daughters (carrying paternal and maternal chromosomes).…”
Section: Discussionmentioning
confidence: 99%
“…We also screened for the presence of the three endosymbionts in all other reported cases of facultative parthenogenesis in the Neotropics: Embiratermes neotenicus and Silvestritermes minutus (Termitidae: Syntermitinae), both restoring ploidy through central fusion (Fougeyrollas et al 2015;Fougeyrollas et al 2017) (heads and gonads of 25 neotenic queens distributed in five nests).…”
Section: Termite Genera Phylogenetically Close To Cavitermes and Repomentioning
confidence: 99%
“…Developmental origin of neotenic parthenogens in C. tuberosus differs from that observed in the two AQS species recently identified in the higher termite subfamily Syntermitinae, that is, Embiratermes neotenicus (Fougeyrollas et al ) and Silvestritermes minutus (Fougeyrollas et al ). In both species, the neotenics differentiate from parthenogenetically produced nymphs of the fourth stage.…”
Section: Discussionmentioning
confidence: 71%
“…This replacement supposedly enhances the reproductive capacity of the colony (Matsuura, ). First reported from Reticulitermes species (Luchetti, Velonà, Mueller, & Mantovani, ; Matsuura et al, ; Vargo, Labadie, & Matsuura, ), AQS was recently demonstrated in several Termitidae (Fougeyrollas et al, , ; Fournier, Hellemans, Hanus, & Roisin, ; Hellemans, Bourguignon, Kyjaková, Hanus, & Roisin, ). Observations on all these species suggest that the caste fate of asexually produced females is determined by their parthenogenetic origin since most parthenogens develop into neotenic queens and only a small portion into other castes (Matsuura, ).…”
Section: Introductionmentioning
confidence: 95%